Safety, Immunogenicity, and Efficacy of COVID-19 Vaccines in Adolescents, Children, and Infants: A Systematic Review and Meta-Analysis - Du, Yuxuan; Chen, Long; Shi, Yuan (Frontiers in Public Health, 2022)
Background: As the epidemic progresses, universal vaccination against COVID-19 has been the trend, but there are still some doubts about the efficacy and safety of COVID-19 vaccines in adolescents, children, and even infants. Purpose: To evaluate the safety, immunogenicity, and efficacy of COVID-19 vaccines in the population aged 0-17 years. Method: A comprehensive search for relevant randomized controlled trials (RCTs) was conducted in PubMed, EMBASE, and the Cochrane Library from inception to November 9, 2021. All data were pooled by RevMan 5.3 statistical software, with risk ratio (RR) and its 95% confidence interval as the effect measure. This study protocol was registered on PROSPERO(CRD42021290205). Results: There was a total of six randomized controlled trials included in this systematic review and meta-analysis, enrolling participants in the age range of 3-17 years, and containing three types of COVID-19 vaccines. Compared with mRNA vaccines and adenovirus vector vaccines, inactivated vaccines have a more satisfactory safety profile, both after initial (RR 1.40, 95% CI 1.04 1.90, P=0.03) and booster(RR 1.84, 95% CI 1.20 2.81, P=0.005) vaccination. The risk of adverse reactions was significantly increased after the first and second doses, but there was no significant difference between the first two doses (RR 1.00, 95%CI 0.99 1.02, P=0.60). Nevertheless, the two-dose regimen is obviously superior to the single-dose schedule for immunogenicity and efficacy. After booster vaccination, both neutralizing antibodies (RR 144.80, 95%CI 44.97 466.24, P<0.00001) and RBD-binding antibodies (RR 101.50, 95%CI 6.44 1600.76, P=0.001) reach optimal levels, but the cellular immune response seemed not to be further enhanced. In addition, compared with younger children, older children and adolescents were at significantly increased risk of adverse reactions after vaccination, with either mRNA or inactivated vaccines, accompanied by a stronger immune response. Conclusion: The available evidence suggests that the safety, immunogenicity and efficacy of COVID-19 vaccines are acceptable in people aged 3-17 years. However, there is an urgent need for additional multicenter, large-sample studies, especially in younger children under 3 years of age and even in infants, with long-term follow-up data.